2005
DOI: 10.1074/jbc.m413458200
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Recombinant Apolipoprotein E Variant with Improved Biological Functions

Abstract: To identify the residues in the carboxyl-terminal region 260 -299 of human apolipoprotein E (apoE) that contribute to hypertriglyceridemia, two sets of conserved, hydrophobic amino acids between residues 261 and 283 were mutated to alanines, and recombinant adenoviruses expressing these apoE mutants were generated. Adenovirus-mediated gene transfer of apoE4-mut1 (apoE4 (L261A, W264A, F265A, L268A, V269A)) in apoE-deficient mice (apoE ؊/؊ ) corrected plasma cholesterol levels and did not cause hypertriglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…In humans and experimental animals plasma apoE levels correlate with plasma triglyceride levels (57,58). On the basis of this information we hypothesized that expression of dn-c-Jun in apoE Ϫ/Ϫ mice would not affect the plasma lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and experimental animals plasma apoE levels correlate with plasma triglyceride levels (57,58). On the basis of this information we hypothesized that expression of dn-c-Jun in apoE Ϫ/Ϫ mice would not affect the plasma lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…High expression levels of hepatic apoE result in a notable increase in VLDL triglyceride secretion (11,12). The C-terminal domain is required for the promotion of VLDL triglyceride secretion, particularly the hydrophobic amino acids between residues 260 and 270 (13). The multiple roles of apoE in VLDL homeostasis are concentration dependent with low levels of apoE sufficient to promote receptor-mediated lipoprotein clearance and higher concentrations required to induce hypertriglyceridemia.…”
Section: Apoe and Triglyceride-rich Lipoprotein Productionmentioning
confidence: 99%
“…Cholesterol input from these lipoproteins induces a downregulation of LDLR and thus a higher concentration of circulating cholesterol (141). It has also been suggested that apoE4-associated hyperlipidemia may be a consequence of deficient lipoprotein lipase activity and/or reduced affinity/visibility of lipoprotein-bound apoE4 (142). The apoE2 and apoE4 phenotypes are associated with increased levels of plasma TGs relative to apoE3.…”
Section: In Peripheral and Brain Lipid Homeostasismentioning
confidence: 99%